Long Time from Diagnosis to Surgery May Increase Postoperative Complication Rates in Elective CD Intestinal Resections: An Observational Study - Paulo Gustavo Kotze; Daniela Oliveira Magro; Carlos Augusto Real Martinez; Antonino Spinelli; Takayuki Yamamoto; Janindra Warusavitarne; Claudio Saddy Rodrigues Coy (Gastroenterology Research and Practice)
Background. There is lack of data analyzing short-term postoperative complications and time from diagnosis to surgery in Crohn’s disease (CD). Aim. To compare complication rates after elective abdominal operations in CD patients with different durations of disease. Methods. Retrospective observational study with CD patients who submitted to elective intestinal resections. Patients were allocated in 2 groups according to time to surgery (TS) in less or more than 5 years. Short-term postoperative complications were analyzed and compared between the 2 groups, and binary logistic regression analysis was performed to check for significant variables. Results. 123 patients were finally included, 77 with TS > 5 years (62.6%) and 46 with TS < 5 years (37.4%). Patients with TS > 5 years had higher rates of overall surgical complications (p=0.011), reoperations (p=0.003), surgical site infections (p=0.014), anastomotic dehiscence (p=0.021), abdominal abscesses (p=0.021), and overall medical complications (p=0.019). On logistic regression, the single significant variable was the confection of stomas (OR: 3.203; 95% CI: 1.011–10.151; p=0.048). Conclusions. Patients with longer time to surgery showed a significant increase in overall medical and surgical postoperative early complications after elective intestinal resections.